2011
DOI: 10.1214/10-aos839
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an anomalous cluster in a network

Abstract: We consider the problem of detecting whether or not, in a given sensor network, there is a cluster of sensors which exhibit an "unusual behavior." Formally, suppose we are given a set of nodes and attach a random variable to each node. We observe a realization of this process and want to decide between the following two hypotheses: under the null, the variables are i.i.d. standard normal; under the alternative, there is a cluster of variables that are i.i.d. normal with positive mean and unit variance, while t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
214
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(218 citation statements)
references
References 66 publications
4
214
0
Order By: Relevance
“…In the detection literature, it is common to show that when a predefined signal strength is sufficiently large, the null and alternative hypotheses are asymptotically distinguishable. Theorem 1 and Corollary 1 follow the same path; see other similar examples in [65], [43], [57], [45], [53].…”
Section: Lemma 2 (Sparsitymentioning
confidence: 61%
See 1 more Smart Citation
“…In the detection literature, it is common to show that when a predefined signal strength is sufficiently large, the null and alternative hypotheses are asymptotically distinguishable. Theorem 1 and Corollary 1 follow the same path; see other similar examples in [65], [43], [57], [45], [53].…”
Section: Lemma 2 (Sparsitymentioning
confidence: 61%
“…Using the definition from [43], [44], [45], we say that H Bernoulli noise model. In this paper, we are particularly interested in (2) with the Bernoulli noise model, f (s, ) = Bernoulli(s + 1 V ) ∈ R N , where each element f (s, ) i is an independent Bernoulli random variable with mean (s + ) i ,…”
Section: Problem Formulationmentioning
confidence: 99%
“…, n}. CDEP as a risk measure has been considered in the literature for detecting abnormal clusters in a network (see e.g., [4,10]). It also provides an upper bound on the Bayesian risk measure.…”
Section: Detection Procedures Based On Generalized Likelihood Ratio Testmentioning
confidence: 99%
“…Several other possible forms of structured activation patterns have also been applied to sparse detection problems. [7] describes detecting sparse binary patterns with a variety of combinatoric structures under Gaussian noise. Lower bounds on minimax detection rates are given, and it is shown that forms of the scan statistic achieve within a log factor of these rates.…”
Section: Sparse Detectionmentioning
confidence: 99%